Effect of Pre- and Post-partum Challenge Feeding on Performance and Serum Mineral Levels of Crossbred Dairy Cattle - Lasna Sahib, Pramod S, Bibin Becha B, Anu P Joseph and Thirupathy Venkatachalapathy R (Indian Journal of Dairy Science, 2022)
The present work was designed to evaluate the effects of pre-and post-partum challenge feeding on the production performance and serum mineral levels of the crossbred dairy cows under farm conditions. The work was scheduled for 21 days pre-partum to 60 days post-partum. Fourteen dry pregnant crossbred cows were divided into two equal groups and were maintained either on control diet (CN) or were challenge fed (CF) with concentrates from 21 days pre-partum to 45 days post-partum and thereafter maintained on the same diet as CN. The dry matter intake was significantly (p